Enhanced Memristive Performance of Double Perovskite Cs2AgBiBr6‐xClx Devices by Chloride Doping. Issue 11 (18th November 2021) - Sun, Caixiang; Luo, Feifei; Ruan, Liuxia; Tong, Junwei; Yan, Linwei; Zheng, Yadan; Han, Xiaoli; Zhang, Yanlin; Zhang, Xianmin
Abstract: Mixed halide perovskites are promising memristive materials because of their excellent electronic‐ionic properties. In this work, lead‐free Cs2 AgBiBr6‐ x Cl x ( x =0, 0.2, 0.4, 0.6, 0.8, 1.0) double perovskite films were fabricated using a one‐step solution spin‐coating method in air. Moreover, the ITO/Cs2 AgBiBr6‐ x Cl x /Al sandwich‐like devices are fabricated to investigate the memristive behaviors. The present memristors exhibit nonvolatile and bipolar resistive switching behaviors without electroforming process. Interestingly, as the chloride content increases, the ON/OFF ratio of the device increases from 10 3 to 10 4, the average SET voltage and the RESET voltage decrease from −0.40 V to −0.21 V and from 1.55 V to 1.34 V, respectively. In addition, resistance states of devices can be maintained after 100 switching cycles and 10 4 s of reading. This study provides new possibility for the development of low‐power and environmentally friendly memristors. Abstract : Lead‐free Cs2 AgBiBr6‐ x Cl x ( x =0, 0.2, 0.4, 0.6, 0.8, 1.0) perovskite films were synthesized and characterized. The ITO/Cs2 AgBiBr6‐ x Cl x /Al devices were fabricated to investigate the memristive behaviors. As the chloride content increases, the ON/OFF ratio of the device increases from 10 3 to 10 4, the average VSET and the VRESET decrease from −0.40 V to −0.21 V and from 1.55 V to 1.34 V, respectively. Resistance states of devices can be maintained after 100 switching cycles and 10 4 s of reading.